Epidemiological Evidence Between Variants in Matrix Metalloproteinases-2, -7, and -9 and Cancer Risk - Huang, Chenglu; Xu, Suqin; Luo, Zhilin; Li, Dong; Wang, Rui; Wang, Tianhu (Frontiers in Oncology, 2022)
Background: Matrix metalloproteinases (MMPs), a kind of proteases, have a critical function in cancer occurrence, invasion and migration. MMPs gene variant (e.g., MMP - 2, -7 and -9) can affect the biological functions of these enzymes and lead to the occurrence and progression of cancer, which has become a hot topic in recent years, but the corresponding results are still controversial. In this context, here, the meta-analysis was conducted for assessing the relations of variants in MMP - 2, -7 and -9 with the risk of various cancers. Methods: PubMed, Web of Science and Medline were systemically searched, and data were extracted from all eligible studies so as to investigate the susceptibility of MMP - 2, -7 and -9 to different types of cancers. The association between variant in MMP and cancer susceptibility was analyzed through odds ratios (OR) as well as 95% confidence intervals (CI). Venice criteria and false positive report probability (FPRP) were adopted to evaluate epidemiological evidence of significant associations discovered. Results: The associations between the variants of MMPs and cancer risk in 36,530 cases and 41,258 controls were found, with 12 associations (MMP-2 rs243865 with esophageal cancer and lung cancer, MMP-7 rs11568818 with bladder and cervical cancer, and MMP-9 rs3918242 with breast cancer) were rated as strong associations for cancer risk, whereas 7 and 15 as moderate and weak associations, respectively. These significant associations were mostly found in Asians. Conclusions: These findings support the relations between variants of MMP-2, -7, and -9 and various cancers risk, demonstrating the credibility of these relations.